PENGGUNAAN STRATEGI PEMBELAJARAN PEER TUTORING UNTUK MENINGKATKAN KREATIVITAS SISWA DALAM MATA PELAJARAN SENI RUPA KELAS VII SMPN 3 PADANG - Putri Sindi, Dra. Zubaidah, M.Pd. (Universitas Negeri Padang, 2019)
The purpose of this research is improve student creativity of fine art major with using Peer Tutoring strategy grade VII-2 SMP Negei 3 Padang. The kind of this researchis is classroom action research which using Peer Tutoring strategy to grade VII-2 SMP Negeri 3 Padang. This researchimplemented in two cycles. Data collection tool used teacher observation sheet, student observation sheet and the format for evaluating student creativity. Data processed by using percentage formula . The result of data processed show that there is increase of learning outcomes. Learning outcome in cycle I is 74,6 and cycle II incre ase until 91,6. The acquisition of learningoutcomes showed the significant increase. It can conclude that the using of Peer Tutoring strategy can increase student creativity.Keywords: Learning, Peer Tutoring, Creativity